Modern chemical synthesis methods towards low-dimensional phase change structures in the Ge–Sb–Te material system. Issue 2 (June 2015) - Hardtdegen, Hilde; Mikulics, Martin; Rieß, Sally; Schuck, Martin; Saltzmann, Tobias; Simon, Ulrich; Longo, Massimo
Abstract: This report centers on different modern chemical synthesis methods suitable for production with which low-dimensional crystalline structures are attainable in the Ge–Sb–Te material system. The general characteristics of the methods are described first. The special challenges are discussed for the Ge–Sb–Te material system. Growth optimization is studied, and the resulting nanostructures are presented. At last a comparison of the methods is given with respect to research scale vapor transport approach on the one hand and the potential described for future application in technology on the other hand.